Baseline assessment of rice farming in Kenya - Villanueva, Donald; Pede, Valerien; Revicoy, Riela; Buvelot, Luc; Enriquez, Yuji; Cabrera, Ellanie; Murori, Rosemary; Menge, Daniel; Musila, Ruth; Kengo, Milton; Ndai, Florence; Ismail, Abdelbagi; et al. (International Rice Research Institute, 2025)
The overall objective of this initiative is for IRRI and its national partners to establish a recurrent system to monitor development in rice-based environments in key focal countries. This study, which was begun for Kenya, aims to understand the status of the rice sector and establish baseline conditions to be used for future impact assessment studies. This initiative aims to continuously monitor key indicators in the rice-growing environments of the country in subsequent years. The first round of this study conducted in 2023 is considered as the baseline and it provides an overview of the rice situation in the major rice-growing regions in the country. We collected data from a total of 729 rice farmers that were randomly selected from the six major irrigation schemes managed by the National Irrigation Authority (NIA) in three primary rice- producing counties: Kirinyaga, Western Kenya which encompasses Kisumu and Busia counties, and Tana River. This comprehensive baseline survey reveals distinct disparities and also some commonalities in the rice sector across the regions under study. The extensive use of hired labor for tasks such as transplanting, fertilizer application, and pest management underscores the need for enhanced mechanization and training to bring efficiency. The disparities in rice production profits across the countries highlight the critical need to address productivity and cost management to enhance profitability uniformly across all three counties. The higher engagement in training and organizational participation in Western Kenya than in the other counties suggests that increasing access to these resources could benefit the overall productivity and sustainability of rice farming. In addition, promoting secure land tenure, mechanization, and value-added activities such as rice straw management can further bolster the sector’s growth and sustainability. This survey establishes a critical foundation for future impact assessments and targeted interventions aimed at enhancing the rice sector in Kenya.